Treatment of Early Stage Non-Small Cell Lung Cancer: Surgery or Stereotactic Ablative Radiotherapy? - Uzel, Esengül Koçak (Balkan Med J, 2015)
The management of early-stage Non-small Cell Lung Cancer (NSCLC) has improved recently due to advances in surgical and radiation modalities. Minimally-invasive procedures like Video-assisted thoracoscopic surgery (VATS) lobectomy decreases the morbidity of surgery, while the numerous methods of staging the mediastinum such as endobronchial and endoscopic ultrasound-guided biopsies are helping to achieve the objectives much more effectively. Stereotactic Ablative Radiotherapy (SABR) has become the frontrunner as the standard of care in medically inoperable early stage NSCLC patients, and has also been branded as tolerable and highly effective. Ongoing researches using SABR are continuously validating the optimal dosing and fractionation schemes, while at the same time instituting its role for both inoperable and operable patients.